Lời giải:
Sử dụng công thức
\(N=a^4+b^4+c^4=(a^2+b^2+c^2)^2-2(a^2b^2+b^2c^2+c^2a^2)\)
\(=14^2-2[(ab+bc+ac)^2-2(a^2bc+b^2ac+c^2ab)]\)
\(=14^2-2[(ab+bc+ac)^2-2abc(a+b+c)]\)
\(=14^2-2(ab+bc+ac)^2(1)\)
Lại có:
\(\left\{\begin{matrix} a+b+c=0\\ a^2+b^2+c^2=14\end{matrix}\right.\Rightarrow \left\{\begin{matrix} (a+b+c)^2=0\\ a^2+b^2+c^2=14\end{matrix}\right.\)
\(\Rightarrow (a+b+c)^2-(a^2+b^2+c^2)=-14\)
\(\Leftrightarrow 2(ab+bc+ac)=-14\Leftrightarrow ab+bc+ac=-7(2)\)
Từ \((1); (2)\Rightarrow N=14^2-2(-7)^2=98\)